Isolation and Characterization of Acinetobacter baumannii Recovered from Campylobacter Selective Medium - Fernando, Dinesh M.; Khan, Izhar U. H.; Patidar, Rakesh; Lapen, David R.; Talbot, Guylaine; Topp, Edward; Kumar, Ayush (Frontiers in Microbiology, 2016)
Acinetobacter baumannii, a Gram-negative opportunistic pathogen, is known to cause multidrug resistant infections. This organism has primarily been isolated from clinical environments and its environmental reservoirs remain largely unknown. In the present study, we recovered seven isolates of A. baumannii growing under conditions selective for Campylobacter spp. (microaerophilic at 42 oC and in the presence of antibiotics) from dairy cattle manure storage tank or surface water impacted by livestock effluents. Antibiotic susceptibility tests revealed that all of these isolates were less susceptible to at least two different clinically relevant antibiotics, compared to the type strain A. baumannii ATCC17978. Expression of resistance-nodulation-division efflux pumps, an important mechanism of intrinsic resistance in these organisms, was analyzed and adeB was found to be overexpressed in one and adeJ was overexpressed in three isolates. Comparison of these isolates using genomic DNA Macro-Restriction Fragment Pattern Analysis (MRFPA) revealed relatively low relatedness among themselves or with some of the clinical isolates from previous studies. This study suggests that A. baumannii isolates are capable of growing under selective conditions for Campylobacter spp. and that this organism can be present in manure and water.